Effects of irradiation sterilization on spices - FU Jun-jie (浙江大学学报. 农业与生命科学版, 2000)
The gamma irradiation effects on sterilization of the spices were studied in the paper, the results showed that the gamma irradiation could effectively kill all microbes in the spices, and irradiated spices could be stored at room temperature for one year. The results of microbiological assay and absorbed dose detection indicated that the optimal dose for spices irradiation ranged from 6 to 12 kGy. The application of the stacking isochronal rotating double-layer irradiation technique could serve the commercialization of spices irradiation.